Report on professional attachment with OCBC Asset Management Limited. - Koon, Yuan Huey. (2008)
The report gave an overview on the companyes structure and its various functions. It also oulines how the attachment to OAM has helped author gain insights to the significance of training in building my knowledge and understanding as well as the importance of relationship building andestablishing good rapport with the colleagues.